The Role of Technology in Education (IntechOpen, 2021)
This book has three sections on the role of technology in education. The first section covers the merits of online learning and environment. The second section of the book gives insight on new technologies in learning and teaching. The third section of the book underlines the importance of new tendencies for the technology in education. I have a firm belief that readers can find great insights on the role of technology in education from different reflections and research.